1988
DOI: 10.1152/jn.1988.59.2.607
|View full text |Cite
|
Sign up to set email alerts
|

Neural mechanisms in vibrotactile adaptation

Abstract: 1. Peripheral and central neural contributions to vibrotactile adaptation were investigated in decerebrate or anesthetized cats by recording from sensory nerve fibers associated with Pacinian corpuscle (PC) receptors and from central neurons of the dorsal column nuclei that receive their input from vibration-sensitive receptors of the forelimb footpads. Responsiveness of units was assessed using 1-s duration, test vibration stimuli delivered with 1- to 2-mm-diam probes at different times following adapting tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
41
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(44 citation statements)
references
References 0 publications
3
41
0
Order By: Relevance
“…Adaptation to prolonged vibrotactile input has been reported at the receptor level [28], as well as in several central sites, including the cuneate nucleus [29], thalamus [30] and cortex [31]. RA1 type neurons are reported to exist in S1 [32] and are known to underlie frequency discrimination in the RA mechanical frequency range [33].…”
Section: Discussionmentioning
confidence: 99%
“…Adaptation to prolonged vibrotactile input has been reported at the receptor level [28], as well as in several central sites, including the cuneate nucleus [29], thalamus [30] and cortex [31]. RA1 type neurons are reported to exist in S1 [32] and are known to underlie frequency discrimination in the RA mechanical frequency range [33].…”
Section: Discussionmentioning
confidence: 99%
“…The fact that prolonged stimulation leads to a reduction in the response of neurons to subsequent stimuli at both the peripheral and central levels of neural processing is well documented Chung et al, 2002;O'Mara et al, 1988). Leung et al demonstrated changes in the firing rate in the periphery at much longer stimulus durations and showed that extended suprathreshold vibratory stimulation applied to the skin results in a desensitization of cutaneous mechanoreceptive afferents.…”
Section: Discussionmentioning
confidence: 99%
“…Adaptation is a nearly ubiquitous phenomenon in sensory systems: it occurs in stages Wright, 1968, 1969), including (to take vibrotactile adaptation as an example) adjustment of responsivity at the receptoral level Leung et al, 2005), in the brainstem (O'Mara et al, 1988), and in the cortex (Lee and Whitsel, 1992). Indeed, research in other senses indicates that feature detectors in the cortex, such as those that mediate detection of spatial frequencies by the visual system, are exquisitely susceptible to adaptation.…”
Section: Spatially Coded Surface Roughness Unaffected By Texture Adapmentioning
confidence: 99%